Novel Aspects on Motor Neuron Disease - Foyaca Sibat, Humberto; de Fátima Ibañez-Valdés, Lourdes (IntechOpen, 2020)
Dedicated to our readers, we include novel information (not reported in IntechOpen's books before) about new contributions of aberrant astrocytes to MND damage and death in the SOD1G93A rat experimental model of ALS; novel genetic studies on ALS; an update of the structural and functional consequences of the spinal muscular atrophy-linked mutations of the survival motor neuron protein; stem cell therapy for MND; and the novel treatment for SMA and ALS in the introductory chapter. This book contains selected peer-reviewed chapters written by international researchers. In this publication, the readers will find a compilation of state-of-the-art reviews about etiology, therapies, investigations, the molecular basis of disease progression and clinical manifestations, and the genetic familial ALS, as well as novel therapeutic modalities. We look forward with confidence and pride to the remarkable role that this book will play for a new vision and mission.